Geographical perspectives of the drought and flood hazard in the arid and semi-arid region of the Cape Province - Myburgh, D W (Department of Environmental and Geographical Science, 2026)
Droughts and floods in South Africa have been studied from various points of view but not from the perspective of how humans respond to their being a hazard to life and property. The research for this thesis was undertaken as a first step towards reducing this deficiency. The purpose has been to provide a broad perspective of these two hazards to serve as a base of information and understanding. and a context for further research. rather than to focus on specific problems in detail. It has been conducted within the general paradigm of hazard geography. Its main emphasis is-to identify the full range of human adjustments and adaptations to the hazards of drought and flood in the local context. and it attempts to evaluate and find explanations for these responses. Firstly the geographical patterns of drought and flood are examined. A method is devised for quantifying the flood hazard. Attention is also given to the role humans have played in increasing the level of hazard by their modification of relationships in the.natural environment. Personal interviews and structured questionaires delivered by mail -were used to collect data mainly from farmers. urban dwellers. local and central government agencies and certain (xiii) private organizations. Contingency tables were employed to assist in the identification of relationships. Responses are examined within the framework of six major types: affecting the cause, modifying the hazard, modifying the loss potential, spreading the losses, planning for losses, and bearing the losses. An important finding is that farmers' responses, whether taken singly or in combination, prove to be ineffective in the provision of adequate protection for them against the adverse consequences of serious drought. The explanation the perceptions of that response behaviour is found to be rooted in people and institut~ons have of these hazards, and in a variety of other factors including previous experience, attitudes towards nature and God, attachment to place, social and cultural constraints, personality, economic and political factors. environmental fit and technical feasibility.